MOLECULAR DOCKING APPROACH OF POTENTIAL ALPHA-GLUCOSIDASE INHIBITORS FROM EXTRACTS COMPOUNDS OF R. TUBEROSA L - Safitri, Anna; Tirto Sari, Dewi Ratih; Roosdiana, Anna; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
The present study investigates anti-diabetic capacity of compounds enclosed in the R. tuberosa L. root extracts by molecular simulation approach to examine the potential of those compounds acting as alpha-glucosidase inhibitors. Compounds chosen were cirsimarin, cirsimaritin, and sorbifolin; quercetin was used for the reference. Those compounds were downloaded from PubChem database, and human alpha-glucosidase 3D structure was obtained from Protein Data Bank. The protein was docked to the flavonoid compounds using HEX 8.0 software and visualized using Discovery Studio 4.1. The interactions of cirsimarin, cirsimaritin, sorbifolin, and quercetin on alpha-glucosidase showed similar binding patterns. They interacted with the active sites of the enzyme, causing inhibition on enzyme activity. The interactions between proteins and ligands were mostly through formation of hydrogen bonds and Van der Waals forces. The binding energy of cirsimarin cirsimaritin, sorbifolin, and quercetin to alpha glucosidase were comparable at -323.3, -279.4, -256.8, and -241.5 cal/mol, respectively. These confirm that compounds contained in the extracts of R. tuberosa L have capacity to be used as inhibitor for alpha glucosidase.